Investors' perceptions of the Delaware Supreme Court decision in Unocal v. Mesa - Kamma, Sreenivas; Weintrop, Joseph; Wier, Peggy (Journal of Financial Economics, 1988)
In 1985 the Delaware Supreme Court allowed the Unocal Corporation to make a tender offer for its own shares to all holders except Mesa Partners II, who were attempting to gain control of Unocal. The Unocal decision and Mesa's response are associated with abnormal losses for shareholders of other Delaware firms that appeared to be targets of hostile takeover attempts at the time. These losses suggest that investors believed the decision would increase Delaware managers' ability to resist takeovers to the disadvantage of target shareholders.